689 Work productivity and activity impairment after total knee arthroplasty: a 6-months prospective study. (24th April 2018) - Hylkema, TH; Selzer, F; Stevens, M; Amick, BA; Katz, JN; Brouwer, S
Abstract : Introduction: Total Knee Arthroplasty (TKA) procedures among working-age patients will rapidly increase. A majority of the patients returns to work after TKA surgery, however, if patients are still limited in daily (work) performance is unknown. Therefore, the aim of this study was to examine impairments in work and activities in TKA patients 6 months postoperative. Moreover, to study associations between preoperative characteristics and impairments in work and daily activities at 6 month follow-up. Methods: A prospective cohort study of patients aged <70 years undergoing TKA in the USA. Preoperative data on age, gender, educational level, BMI, pain catastrophizing, pain, function, mental health, knee-related quality of life and health-related quality of life were gathered. At 6 month follow-up patients completed the Work Productivity and Activity Impairment (WPAI) questionnaire, a well validated instrument to measure the effect of the TKA on work productivity and daily activities. Uni- and multivariate linear regressions were used to analyse the association between baseline independent variables and WPAI scores at 6 month follow-up. All models were adjusted for age, gender and BMI. Results: Of the 183 patients included (mean age 61, women 62.3%), 74 reported missing work in the past weeks, accounting for 3.4% of their working time (absenteeism). On average 20.3% of their working time was impaired due to problems of their TKA (presenteeism). In addition, 22.8% of the patients' regular daily activities were impaired due to their TKA (activity impairment). A higher level of pain catastrophizing preoperatively was found as a predictor for presenteeism (Beta 0.35, p<0.001) and activity impairment (Beta 0.47, p<0.001). Discussion: TKA patients are not often absent from work, but do report impairments in daily functioning, including work. Future interventions should focus on TKA patients with high levels of pain catastrophizing preoperatively.